2000
DOI: 10.1139/x99-204
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation changes through time on islands of Lake Duparquet, Abitibi, Canada

Abstract: Succession after fire has mainly been studied by chronosequence, which does not allow study of pre- and post-fire communities at the same site. By using palynology and anthracology, we recovered vegetation communities and fire histories through time on islands of Duparquet Lake, Canada. We show that succession after fire is dependent on interval between two fires (evaluated with depth of humus between subsequent fires). Sites with high fire occurrence show a cyclic succession (same species reappearing after fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Whereas jack pine begins storing seeds younger than black spruce (about 5-10 vs. 30-40 years; Burns & Honkala 1990), earlier stem mortality results in a pineto-spruce density ratio of canopy-stored seeds that progressively decreases during succession (Pinard 1999). Accordingly, it has been observed that short fire intervals tend to increase relative pine abundance compared with pre-fire conditions, whereas longer intervals tend to increase spruce abundance (Lavoie & Sirois 1998;Larocque et al 2000). Jack pine has thicker cone scales, and reduced seed mortality during severe crown fire (Beaufait 1960;Zasada et al 1979;Arseneault 2001) may also contribute to trends in species abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas jack pine begins storing seeds younger than black spruce (about 5-10 vs. 30-40 years; Burns & Honkala 1990), earlier stem mortality results in a pineto-spruce density ratio of canopy-stored seeds that progressively decreases during succession (Pinard 1999). Accordingly, it has been observed that short fire intervals tend to increase relative pine abundance compared with pre-fire conditions, whereas longer intervals tend to increase spruce abundance (Lavoie & Sirois 1998;Larocque et al 2000). Jack pine has thicker cone scales, and reduced seed mortality during severe crown fire (Beaufait 1960;Zasada et al 1979;Arseneault 2001) may also contribute to trends in species abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Payette et al 2000;Lesieur et al 2002;Lecomte et al in press). This co-occurrence can be strongly linked to site specific historical fire regimes (Larocque et al 2000;Johnstone & Chapin in press). Short fire intervals tend to favour tree species that reach sexual maturity quickly -e.g.…”
Section: Introductionmentioning
confidence: 99%
“…forest ecosystems (Gower et al ., 1997; Bisbee et al ., 2001), but few C budgets available for other successional stages. A few chronosequence studies of boreal forests have focused on vegetation or nutrient changes (Black & Bliss, 1978; Pastor et al ., 1987; Viereck et al ., 1993; Lavoie & Sirois, 1998; Larocque et al ., 2000), but few C budgets during postfire succession exist (Kasischke et al ., 1995; Wirth et al ., 2002). Forest age distribution has a profound effect on C budgets, and has to be taken into account when extrapolating stand‐level C budgets to landscape or regional scales (Schimel, 1995; Chen et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%